Functional chromatography reveals three natural products that target the same protein with distinct mechanisms of action - Kang, MinJin (2014)
Access to lead compounds with defined molecular targets continues to be a barrier to the translation of natural product resources. As a solution, we have developed a system that uses discreet, recombinant proteins as the vehicles for natural product isolation. Here, we describe the use of this functional chromatographic method to identify natural products that bind to the AAA+ chaperone, p97, a promising cancer target. Application of this method to a panel of fungal and plant extracts identified rheoemodin, 1-hydroxydehydroherbarin and phomapyrrolidone A as distinct p97 modulators. Excitingly, each of these molecules displayed a unique mechanism of p97 modulation. This discovery provides strong support for the application of functional chromatography to the discovery of protein modulators that would likely escape traditional high-throughput or phenotypic screening platforms.